RANCANG BANGUN SISTEM MONITORING PENGGUNAAN BAHAN BAKAR MINYAK (BBM) DAN TEMPERATUR PADA GENERATOR MENGGUNAKAN SMS BERBASIS PENGENDALI MIKRO - Indra Kurniawan . (Faculty of Engineering, Universitas Tanjungpura, 2015)
ABSTRACT Monitoring the consumption of fuel and the temperature on a generator is important to retain a backup power source of the generator without running out of fuel or causing a high temperature in the generator. The design of the monitoring system could detect changes in the condition of the fuel and temperature simultaneously when the generator is in operation. This monitoring system process used an ultrasonic censor to detect the consumption of fuel that is attached to the oil tank and a temperature censor to detect temperature changes in the generator mounted on the body of the generator. The ultrasonic censor output voltage and temperature censor were the converted by the Analog To Digital (ADC) Internal microcontroller ATMega16. This system design was divided into 10 scale percentage unit (%) for the consumption of fuel and a celsius unit (° C) of the temperature measurement for the changes of the temperature of the generator. The data detected by the censors instalated would be processed by the microcontroller and the sent through Wavecom Fastrack M1206B modem to celluler phone in the form of a text messageof the short message service (SMS), sent through Wireless Radio Telemetry Kit 915MHz to a computer/laptop which was shown ina graphical form, displaying the monitored data by using the 16 x 4 LCD display. Keyword : Microcontroller, Monitoring, Temperature,Generator, Short Message Service (SMS)